2019
DOI: 10.1002/dev.21840
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol as a measure of the stress response to social adversity in young children

Abstract: Hair cortisol has the potential to provide insight into young children's long-term stress response to social adversity. This study investigated associations between children's exposure to adversity from pregnancy to 2 years of age and their hair cortisol at 2 years, using a longitudinal cohort of children enriched for adversity risk, whose mothers were recruited during pregnancy through the "right@home" trial. Exposures were 18 maternal socioeconomic and psychosocial indicators of adversity, examined as concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…In addition, the non-significant association between hair cortisol in children and parenting stress of the parents may indicate that the parenting stress perceived by the parents does not translate directly into children's experienced stress e.g., 64 . Alternatively, there may not be a reliable association of hair cortisol levels and stress exposure in children who were not institutionalized or maltreated e.g., 67,68 . Overall, this is in line with the notion that stress and cortisol have a complex, and yet poorly understood relationship 60 .…”
Section: Regression Pathsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the non-significant association between hair cortisol in children and parenting stress of the parents may indicate that the parenting stress perceived by the parents does not translate directly into children's experienced stress e.g., 64 . Alternatively, there may not be a reliable association of hair cortisol levels and stress exposure in children who were not institutionalized or maltreated e.g., 67,68 . Overall, this is in line with the notion that stress and cortisol have a complex, and yet poorly understood relationship 60 .…”
Section: Regression Pathsmentioning
confidence: 99%
“…Importantly, this may also negatively affect neural maturation: low levels of glucocorticoids can negatively affect neurogenesis in interaction with BDNF 66 . Other studies report weak and inconsistent associations 61,67,68 or null results 67 on adversity and cortisol concentrations in children. A recent meta-analysis on the association between adversity and hair cortisol levels confirms that adversity can be associated with both higher and lower hair cortisol levels and that the small association is moderated by type and timing of adversity, and sample characteristics 69 .…”
mentioning
confidence: 99%
“…Further, one of the mechanisms through which early adversities are postulated to lead to poor child outcomes is through the dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis which controls an individual's response to stressful situations. While earlier studies have examined salivary cortisol as a marker of physiological stress 24 , hair cortisol concentration have recently gained prominence as a reliable marker of chronic HPA axis activity in children [25][26][27][28][29] . However, the prospective association between hair cortisol levels with later child outcomes has been described in only three studies [30][31][32] , with common childhood diseases, child mental health, and physical and mental well-being being the primary outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…While earlier studies have examined salivary cortisol as a marker of physiological stress 24 , hair cortisol concentration have recently gained prominence as a reliable marker of chronic HPA axis activity in children [25][26][27][28][29] . However, the prospective association between hair cortisol levels with later child outcomes has been described in only three studies [30][31][32] , with common childhood diseases, child mental health, and physical and mental well-being being the primary outcome measures. Second, the putative causal mediation role of hair cortisol levels on the association between cumulative adversities and later growth and cognitive outcomes in children has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Usually stress has been measured using cortisol concentrations in saliva, blood and urine at a single time point (Wells et al, 2014), however, a newly established technique using hair cortisol concentrations provides a measure of retrospective chronic stress (Russell et al, 2012). While there are some mixed conclusions about the use of hair cortisol as a measure with very young children (Bryson et al, 2019), higher hair cortisol has been found to be associated with chronic stress including chronic pain, unemployment, shift work, serious life events, and psychopathology in adults (Staufenbiel et al, 2013). In order to examine whether TOTS reduced stress in parents and toddlers, the study included hair samples to measure systemic cortisol with the expectation that those in the intervention condition would have lowered parental and toddler stress after the program.…”
Section: Introductionmentioning
confidence: 99%